Peranan Audit Forensik Dalam Pencegahan Kasus Fraud Penerbitan Izin Usaha Pertambanga (IUP) Pemerintahan Daerah - Aryanto Nur (LPPM Universitas Dharma Andalas, 2022)
Fraud is a latent danger that threatens a country. The occurrence of fraud (cheating) in the public and private sectors has an extraordinary loss impact. Research results from the Association of Certified Fraud Examiners (ACFE) Global show that every year an average of 5% of the organization's revenue becomes a victim of fraud. Fraud is an unlawful act that is intentionally carried out for a specific purpose (manipulation or giving false reports to other parties) carried out by people from inside or outside the organization to gain personal or group benefits that directly or indirectly harm other parties. The research uses qualitative methods with data collection methods using literature studies. The object of this research is secondary data in the form of fraud against licensing by local governments. For this reason, the role of forensic audits is the best way to prevent and detect fraud. Forensic audits have the ability to provide statements in their expertise.